Evolving sophistication of trade patterns in a transition economy - machinery exports of Poland 1980-2009 - Kellman, Mitchell H.; Shachmurove, Yochanan (Economics and Business Review, 2012)
Polish history leads to an expectation of exceptional adaptability to changes in the international economic environment. In the period bigenning with Solidarity at Gdansk to the present, Poland has faced huge structural dislocations. Is there any objective indication that the structural changes needed to successfully compete as a full-fledged European Union member were forthcoming? This study examines the behavior of four separate measures of embodied "sophistication." Though methodologically unrelated, these disparate indices tell a common story of rapid and substantial progress in the "battlefield" of a new member of the European Union. (original abstract)